The Association between Spatiotemporal Gait Asymmetry and Walking Balance in People Post Stroke - Mania Sheikh; Hossein Asghar Hosseini (Shiraz University of Medical Sciences, 2019)
Background: Falls are a common complication post-stroke and often induce due to poor balance. Given that falls often occur during walking, it is possible that gait patterns influence balance during walking. Walking post-stroke is frequently spatiotemporally asymmetric, which may reduce walking balance. The aim of this study was to determine the relationship between gait asymmetry and walking balance in persons with chronic stroke. Methods: Fifty-four persons with chronic stroke (34 men and 20 women) with the mean age of 57.28 participated in this cross-sectional study. Participants walked at their self-selected speed to calculate gait asymmetry ratios for stance time, swing time, and step length. The data were collected using a conventional camera with a sampling frequency of 60 Hz. Reflective markers were attached to the heel and toe regions. Participants also performed walking balance tests including Functional Gait Assessment (FGA) and Mini Balance Evaluation System Test (Mini-BESTest). Pearson correlation test was used to determine the relationships between gait asymmetry and walking balance. Results: The mean±standard deviation values of stance, swing and step asymmetry ratios and FGA and Mini-BESTest were 1.2±0.11, 1.43±0.24, 1.25±0.15, 24.11±2.93 and 22.87±2.29, respectively. Increased FGA and Mini- BESTest scores were related to decreased swing (r=-0.64, P≤0.001 and, r=-0.71, P≤0.0001, respectively) and step asymmetry (r=-0.41, P≤0.002 and, r=-0.51, P≤0.001, respectively). No significant relationship was identified between FGA, and Mini-BESTest and stance asymmetry (r=-0.25, P≤0.06 and r=-0.23, P≤0.08 respectively). Conclusion: According to the current results spatiotemporal gait asymmetry may be related to decreased balance during walking in individuals with chronic stroke suggesting that rehabilitation interventions should focus specifically on ameliorating spatiotemporal gait asymmetry.